PROBLEMS OF TAXATION OF SMALL BUSINESSES - Kratt, Oleg; Byrdeina, Yulia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The problems of taxation of small businesses are considered. The impact of a small enterprise on the country’s economy is reflected. Ways to solve the problem of taxation in small business are proposed.